(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تضمّن البحث إجراء تحاليل فصلية دورية فيزيائية وكيميائية لمياه الصرف الصحي المعالجة في ريف اللاذقية على مدى عام 2011 , باختبار ثلاث محطات معالجة متشابهة في آلية العمل متوزعة في ثلاث قرى هي (حبيت – الحارة – مرج معيربان). شملت الدراسة قياس درجة الحرارة ، والرقم الهيدروجيني، والأوكسجين المذاب والعكارة, وأيضاً تحديد كلٍّ من أيونات النترات ، والفوسفات ، والكبريتات , والكلوريد. استخدمت في هذه الدراسة الطريقة الكمونية باستخدام المساري الانتقائية للأيونات ISEs ، والتحليل الطيفيّ المرئي والتحليل التوربيدي متري. أظهرت النتائج وجود فروقات كبيرة في تراكيز الأيونات المدروسة عند الانتقال من محطة إلى أخرى ,إذ سجلت أعلى التراكيز لأيون النترات في محطة حبيت , وبخاصة في فصل الصيف حيث بلغ (228.33mg/L). أما بالنسبة إلى تراكيز أيون الفوسفات فسجل أعلاها في محطة حبيت في فصل الصيف (41.81mg/L). بينما سجلت أعلى التراكيز لأيون الكبريتات في محطة الحارة في جميع الفصول, وتراوحت بين mg/L(508.67-1157.33)، في حين سجل أعلى تركيز (310.33mg/L) بالنسبة لأيون الكلوريد في محطة حبيت صيفاً. درست النتائج إحصائياً فأعطت قيماً لمعاملات الارتباط قوية أحياناً وضعيفة أحياناً أخرى, مما يعطي مؤشرات واضحة عن مصادر التلوث. This research has included quarterly and periodically physical and chemical analysis of treatment wastewater in the Latakia countryside during year 2011 by testing three treatment plants similar in the mechanism of action and distributed in three villages (Happit, Al-Harah, Marg Moairban). This study has included the measurement of temperature, pH, dissolved oxygen, turbidity, and determination of nitrate, phosphate, sulfate, and chloride. In this research, potentiometric using Selective Electrodes ISEs, the Visible Spectrum, and the Turbidimetry methods were used. The results showed significant differences in concentrations of the studied ions between one station to another. The highest nitrate concentrations (228.33mg/l) were recorded in Happit treatment plant especially in summer, and the highest phosphate concentrations (41.81mg/l) were in Happit treatment plant in summer. Whilst the highest sulfate concentrations which ranged between (508.67– 1157.33)mg/l were in Al-Harah treatment plant at all seasons. The highest chloride concentrations (310.33mg/l) recorded in Happit treatment plant in summer. The statistical study has demonstrated and showed high and sometimes low correlation coefficient R2 so that gives clear indications about the sources of pollution.